1992
DOI: 10.1111/j.2042-3306.1992.tb02778.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on the vascular anatomy of the equine superficial digital flexor tendon

Abstract: Summary The vascular and microvascular anatomy of normal equine superficial digital flexor tendons was studied by dissection of vinyl‐perfused specimens and by microangiography on high detail film. The presence of an extensive intratendinous vascular latticework was confirmed, and a ‘nutrient artery’ described closely associated with the accessory ligament of the superficial digital flexor tendon (proximal check ligament). Circumferential stripping of the paratenon from the tendon to eliminate afferent vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 23 publications
1
33
0
3
Order By: Relevance
“…Work done by Kraus-Hansen et al using horses involved disrupting the vascular supply to the paratendious area (72). After exercise, the paratenon was thickened, and the vascularity of the structure increased with no accompanying change in the tendon itself.…”
Section: Mechanical Behavior Of Tendonsmentioning
confidence: 98%
“…Work done by Kraus-Hansen et al using horses involved disrupting the vascular supply to the paratendious area (72). After exercise, the paratenon was thickened, and the vascularity of the structure increased with no accompanying change in the tendon itself.…”
Section: Mechanical Behavior Of Tendonsmentioning
confidence: 98%
“…Recent studies have shown that the equine SDF tendonitis in the acute phase starts with the degeneration of microvascular hemorrhage in the endotendineum and that the region of degeneration is extended toward the endotendineum in the next phase [1,9]. The variation in the cellular immune response on the ground of cytokines may reflect the physiological/pathological conditions of the SDFT.…”
mentioning
confidence: 99%
“…Tendonitis in the horse is primarily associated with muscular fatigue, inadequate vascular supply and collagen fiber ruptures due to overstrain and overheating of the tendon during exercise (Kraus-Hansen et al 1992, Watkins 1992, Patterson-Kane et al 1997, Patterson-Kane et al 1998, Cherdchutham et al 2001, Yamasaki et al 2001, Oikawa & Kasashima 2002. The SDFT resistance can easily be exceeded if the horse is fatigued or moves in an uncoordinated manner, which can lead to partial or total rupture (Batson et al 2003).…”
Section: Introductionmentioning
confidence: 99%